Pengembangan LKPD Digital Berbasis Inkuiri untuk Meningkatkan Hasil Belajar Fisika - Febryanti Ginting; Irham Ramadhani (Mataram University, 2026)
Physics learning requires teaching materials that can encourage active student involvement so that learning becomes more meaningful and supports improved learning outcomes. The current state of physics instruction at SMA Negeri 1 Berastagi reveals a reliance on conventional teaching methods, a lack of variety in teaching materials, and an absence of digital student worksheets (LKPD). This study aims to develop an inquiry-based digital student worksheet using the Liveworksheets platform for the topic of Temperature and Heat, and to assess its validity, practicality, and impact on student learning outcomes. The study employs the Research and Development (R&D) method using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. Participants included Grade XI F2 and XI F3 students from SMA Negeri 1 Berastagi who took part in both small-group and large-group trials. Data were collected through validation sheets completed by media and subject matter experts, response questionnaires from educators and students, and learning outcome tests. The results indicate that the developed inquiry-based digital worksheet (supported by Liveworksheets) achieved excellent validity ratings from both media and subject matter experts. The product also received highly positive feedback from educators and students, placing it in the